The Rorschach Test Evaluation in Chronic Childhood Migraine: A Preliminary Multicenter Case–Control Study - Esposito, Maria; Messina, Antonietta; Monda, Vincenzo; Bitetti, Ilaria; Salerno, Filomena; Precenzano, Francesco; Pisano, Simone; Salvati, Tiziana; Gritti, Antonella; Marotta, Rosa; Lavano, Serena Marianna; Lavano, Francesco; et al. (Frontiers in Neurology, 2017)
Object Migraine headache prevalence ranges from 1.2 to 3.2% at 7 years of age, increasing with age up to 4-19% in adolescents.1 The aim of the present study is investigating the personality style associated with children and adolescent affected by Migraine without aura (MwA), through administration of the projective Rorschach test and statistical comparison with a group of age- and sex matched healthy controls. Methods 137 patients (74 males and 63 females), aged 7.3–17.4 years (mean age 11.4, SD 3.02 years), affected by MwA according to the IHs-3 criteria. The projective Rorschach test has been administrered to all the cases and controls. Statistical comparisons of groups were performed through comparison of mean values using Student’s t-test for the Rorschach variables treated as numerical variables (R, W%, W+%, D%, F%, F+%, R% l.t., F+% l.t. A%, H%, Anat%, Ban% and Orig%). P-values ,0.05 were considered statistically significant. For statistical analysis, the software STATISTICA (data analysis software system, version 8.1; StatSoft, Inc., 2001) was used. Results No statistical differences were found between the MwA and healthy control group for age (p=0.55), and sex distribution (p=0.804). From the comparison between the two samples MwA group shows lower W responses (p<0.001), good quality W responses (p<0.001), increased frequency of detailed responses (p<0.001), the presence of even minor form of good quality responses (p<0.001), increased presence of animals answers (A%) (p<0.001), more frequent trivial answers (Ban%) (p<0.001). Discussion Rorschach interpretation pinpointed many interesting and, perhaps, peculiar aspects in our MwA population such as a trend predisposition for: analytical reasoning rather than synthetic, ease/practicality rather than creativity, oppositionality rather than external adaptation to the environment that may be interpreted as effect of general maladaptivity.